Analisis Biodiversitas dan Fungsi Lamun Sebagai Spawning Ground Ikan Siganus spp. di Pesisir Perairan Pulau Numfor Provinsi Papua - Rejauw, Korinus; Manalu, Khristhoper Aris. A; Dimara, Lisiard; Kainama, Tamara L.J (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2023)
Local people on Numfor Island are very dependent on coastal and marine natural resources around it, including making seagrass ecosystems as an area to find and capture various marine life to meet their daily needs. Intensive fishing activities cause stress on seagrass ecosystem biota, one of which is Siganus spp. It is known, that some Siganus fish live and breed in seagrass ecosystems, so the existence of habitat and the continuity of their life cycle needs to be studied for scientific data on Numfor Island. The objectives of this study are: (1) analysing seagrass biodiversity, and (2) identifying spawning ground Siganus spp. The research method used is a survey, while data collection is through square line transect techniques, in situ measurements, and interviews (questionnaires). The results of the study obtained are: [1] Seagrass dominance index is low; [2] The Shannon-Wiener Index (H') is moderate at Kansai, Kornasoren, and Andei stations, while at Bawei, Mandori, and Wansra stations are low; [3] Seagrass evenness index is classified as the community in stable condition at Kansai and Bawei stations, while at Kornasoren, Andei, Mandori, and Wansra stations classified as community in unstable condition; and [4] The identified spawning ground locations of Siganus spp. fish on Numfor Island are Kansai, Bawei, Mandori, and Wansra stations. This study concludes that there are no dominant seagrass species and stable ecosystems, medium and low diversity with moderate and severe ecological (environmental) pressures, and seagrass uniformity in stable and unstable conditions